Pengaruh Variasi FFD pada Anoda Heel Effect Terhadap Kualitas Citra Radiografi Melalui Parameter Pixel Value - Sitti Normawati; Syahrir Syahrir; Nur Fitri Qalbina Syahdan; Jumardin Jumardin (Pakis Journal Institute, 2026)
This study aimed to analyze the effect of variations in focus-to-film distance (FFD) on the anode heel effect and radiographic image quality, based on the Pixel Value (PV) parameter. A quantitative experimental approach was employed. The testing was conducted using a phantom articulatio genu with FFD variations of 90 cm, 100 cm, and 120 cm, and object positions varied between the cathode and anode sides. The results indicated that the anode heel effect was more effectively utilized at shorter FFD when the thick side of the object was positioned on the cathode side. The highest PV value was obtained under this condition, whereas a decrease of approximately 11% was observed when the thick side was positioned on the anode side. Furthermore, an FFD of 100 cm produced lower PV standard deviation (PVSD) values, resulting in more homogeneous images with minimal noise. These findings demonstrate that variations in FFD and object positioning influence the distribution of X-ray intensity and radiographic image quality. Appropriate selection of FFD and placement of the thick side of the object on the cathode side can produce more uniform radiographs in terms of sharpness, brightness, and density.